2014
DOI: 10.4315/0362-028x.jfp-13-426
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus G2P[4] Detection in Fresh Vegetables and Oysters in Mexico City

Abstract: Rotaviruses are the principal cause of dehydration caused by diarrhea in children younger than 2 years of age. Although these viral infections have mainly been associated with ingestion of fecally contaminated food and water, few studies have addressed the presence of the virus in food that is consumed raw or slightly cooked. In this work, 30 oyster samples and 33 vegetable samples were examined for the presence of rotavirus genotypes to evaluate their potential to produce gastrointestinal infections. The rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…In this study, the authors showed no correlation between culturing and RT-PCR assays after treatment of RVA with ClO 2 , suggesting that the current chlorine disinfection process may be inadequate to manage the risk of waterborne RVA infections. El-Senousy et al (2014) conducted a study in Egypt in which human and animal RVA (Wa and SA11 strains) were exposed to different chlorine concentrations in inoculated Nile river water and drinking water samples. Both human and animal RVA were more resistant to chlorine in drinking water where only 3 log 10 reduction under 3 mg/l for 15 min was observed while 5 log 10 reduction was observed under exposure to 4 mg/l for 15 min.…”
Section: Chlorinationmentioning
confidence: 99%
“…In this study, the authors showed no correlation between culturing and RT-PCR assays after treatment of RVA with ClO 2 , suggesting that the current chlorine disinfection process may be inadequate to manage the risk of waterborne RVA infections. El-Senousy et al (2014) conducted a study in Egypt in which human and animal RVA (Wa and SA11 strains) were exposed to different chlorine concentrations in inoculated Nile river water and drinking water samples. Both human and animal RVA were more resistant to chlorine in drinking water where only 3 log 10 reduction under 3 mg/l for 15 min was observed while 5 log 10 reduction was observed under exposure to 4 mg/l for 15 min.…”
Section: Chlorinationmentioning
confidence: 99%
“…Blastocystis has been suspected of being associated with irritable bowel syndrome (IBS) (Yakoob et al, 2004;Ustün and Turgay, 2006;Vargas-Sanchez et al, 2015). Regional data on disease burden of Blastocystis infection associated with IBS have been reported from 48 states in the US, Argentina, Switzerland, and Chile (FAO/WHO, 2014). Increased prevalence of Blastocystis in IBS patients compared with controls has been demonstrated (Yakoob et al, 2004;Dogruman-Al et al, 2010;Yakoob et al, 2010).…”
Section: Symptomatologymentioning
confidence: 99%
“…There are 15,000 estimated annual cases of foodborne RV infections in the United States (Scallan et al., ; Scharff, ). RV has been detected in fresh vegetables such as coriander, parsley, celery, spinach, cherry, strawberry, and lettuce in Mexico City (Parada‐Fabian, Juarez‐Garcia, Natividad‐Bonifacio, Vazquez‐Salinas, & Quinones‐Ramirez, ; Quiroz‐Santiago, Vazquez‐Salinas, Natividad‐Bonifacio, Barron‐Romero, & Quinones‐Ramirez, ), in lettuce in Costa Rica and the United States (Aw, Wengert, & Rose, ; Hernandez, Monge, Jimenez, & Taylor, ), and in packaged leafy greens and field‐grown strawberries in Canada (Brassard, Gagne, Genereux, & Cote, ; Mattison et al., ). In addition to being detected in fresh vegetables, RV is also prevalent in irrigation water, untreated and treated wastewater, and river water (Kitajima et al., ; Kiulia et al., ; Lodder & de Roda Husman, ; Prez et al., ).…”
Section: Introductionmentioning
confidence: 99%